Access and Utilization of Information and Communication Technology by Students With Visual Impairment in Uganda's Public Universities - Patrick Ojok (The Center for Disability Studies and Services Brawijaya University, 2018)
The centrality of information and communication technology in enhancing inclusive teaching and learning makes their access and use an imperative for all students at all levels of education.Persons with visual impairment tend to face major barriers in using the same ICT devices that ordinary persons and other disabled persons can use. A quantitative study was conducted with 35 students with visual impairment enrolled in two public universities in Uganda to explore the extent to which they accessed and utilized ICTs. Data was collected using face-to-face interviews and analyzed using IBM SPSS version 20. The study found that most of the students were intermediate ICT users (40%) or beginners (37%), while a majority (70.4%) connected to the internet via WIFI hotspots. More than half of the students (60%) knew that their university had an e-learning platform, but a majority of the students had never uploaded/downloaded any learning materials from their universities' websites.Â Less than half of the students (46%) were confident to produce text using a word processing program but only few could use power point (12%) and excel (8.6%) applications. To improve students with disabilities' access and use of ICTs, multiple actions are required, including equipping departments with computers, ensuring the computers are in accessible locations, giving the students opportunity to practice, and purchasing licensed adapted software applications.